Bycatch of the Indo-Pacific bottlenose dolphin (Tursiops aduncus) in gillnet fisheries off Amakusa-Shimoshima Island, Japan - Shirakihara, Miki; Shirakihara, Kunio (J. Cetacean Res. Manage., 2023)
A year-round resident population of the Indo-Pacific bottlenose dolphin (Tursiops aduncus) inhabits the waters off Amakusa-Shimoshima Island (32°25′N, 130°05´E), in Japan. The effect of bycatch in gillnet fisheries on the Amakusa population was examined. Population size in 2007 and 2008 was estimated at 230 individuals (CV = 2.5%) and 216 individuals (CV = 2.1%), respectively, based on a mark-recapture technique. The magnitude of bycatch was evaluated by analysing interview surveys (263 gillnetters) during these two years. Minimum numbers of dolphin bycatch were 12 individuals in 2007 and 14 individuals in 2008. Most of the dolphins, which were captured by bottom-set gillnets, were considered to be Indo-Pacific bottlenose dolphins for the following reasons: (1) two individuals were identified based on DNA analysis; (2) only Tursiops sp. and finless porpoises were found in the sighting survey by ferry boats, and fishermen can distinguish between the two; and (3) the seasonal and spatial distribution of bycatch corresponded well to habitat use patterns of the Amakusa population. If the US potential biological removal (PBR) approach is used it estimates two individuals per year, which is much lower than the minimum bycatch numbers of 12–14 individuals per year (5.2–6.5% of abundance estimates). Reducing bycatch mortality caused by bottom-set gillnets is essential for the effective conservation of Indo-Pacific bottlenose dolphins in Amakusa, Japan.